POLITENESS STRATEGIES USED BY ELE PRE-SERVICE TEACHERS DURING CLASSROOM TEACHING PRACTICES - Ari Wiryadi Joni, Dewa Ayu; Putu Ayu Paramita Dharmayanti (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2025)
Teaching practice (PLP II) is considered a compulsory subject for pre-service teachers (PSTs). This agenda is done to equip PSTs with experiences to teach in real-world settings. This study belonged to qualitative study which aimed at analyzing politeness strategies employed by ELE pre-service teachers (PSTs) of FKIP Universitas Mahasaraswati Denpasar in academic year 2024/2025 during their teaching practices in SMK Rekayasa Denpasar. There were two ELE PSTs being observed. The data were gathered through video recordings of ELE PSTs’ teaching practices in classrooms. The utterances were analyzed using Brown & Levinson’s politeness strategies. It was found that positive politeness strategies were the most employed, followed with negative politeness strategies. The ELE PSTs also used bald-on-record strategies. However, they rarely used off-record strategies. This study showed that ELE PSTs used politeness strategies to maintain social relationships with the students, create supportive learning environment, and encourage students’ active participation.